CURRENT METHODS DESIGN INNOVATION OF EMISSIONS MEASUREMENT (Perner's Contacts, 2015)
This article deals with the current methods of measuring innovation performance of vehicles in operation. Measurements are performed at regular intervals and measurement methodology is a middle way between the cost of performed measurement and presentation skills test. The reason for upgrading the current methods of measuring emissions is to find the highest number of vehicles that produce unacceptably high levels of harmful emissions, since these emissions threaten not only human health but also the environment.
Keywords: transport, emissions measurement, emission control station